Innovative sponge-based moving bed–osmotic membrane bioreactor hybrid system using a new class of draw solution for municipal wastewater treatment. (15th March 2016) - Nguyen, Nguyen Cong; Chen, Shiao-Shing; Nguyen, Hau Thi; Ray, Saikat Sinha; Ngo, Huu Hao; Guo, Wenshan; Lin, Po-Hsun
Abstract: For the first time, an innovative concept of combining sponge-based moving bed (SMB) and an osmotic membrane bioreactor (OsMBR), known as the SMB-OsMBR hybrid system, were investigated using Triton X-114 surfactant coupled with MgCl2 salt as the draw solution. Compared to traditional activated sludge OsMBR, the SMB-OsMBR system was able to remove more nutrients due to the thick-biofilm layer on sponge carriers. Subsequently less membrane fouling was observed during the wastewater treatment process. A water flux of 11.38 L/(m 2 h) and a negligible reverse salt flux were documented when deionized water served as the feed solution and a mixture of 1.5 M MgCl2 and 1.5 mM Triton X-114 was used as the draw solution. The SMB-OsMBR hybrid system indicated that a stable water flux of 10.5 L/(m 2 h) and low salt accumulation were achieved in a 90-day operation. Moreover, the nutrient removal efficiency of the proposed system was close to 100%, confirming the effectiveness of simultaneous nitrification and denitrification in the biofilm layer on sponge carriers. The overall performance of the SMB-OsMBR hybrid system using MgCl2 coupled with Triton X-114 as the draw solution demonstrates its potential application in wastewater treatment. Graphical abstract: Highlights: A mixture of MgCl2 and Triton X-114 can serve as a novel draw solution. The reverse flux of novel draw solution was 4.5 times lower than that of only MgCl2 . Low salt accumulation was achieved during 90-day SMB-OsMBR operation. Approximately 100% NH4 –N and 98% PO4 –P were removed by the SMB-OsMBR hybrid system. Moving free sponge carriers in the bioreactor continuously cleaned the FO membrane.